Perinatal outcomes in adolescent pregnancy - Dwa, Yam Prasad; Bhandari, Sunita; Shrestha, Devendra; Dhakal, Ajaya Kumar (Journal of Chitwan Medical College, 2018)
Introduction: Adolescent pregnancy is prevalent in Nepal and bears significant consequences to both mother and newborn. Methods: All pregnant women aged 19 years or less who were admitted for delivery at KIST Medical College during 14th April 2017 to 15th July 2018 were included in this study. Maternal and immediate neonatal outcomes were analyzed retrospectively from their medical records. Results: There were 135 pregnant adolescent women out of 1300 deliveries. Preeclampsia was observed in 2 pregnancies. Vaginal delivery (99; 73.3%) was the predominant mode of delivery. Emergency LS CS was performed in 35 (25.9%) deliveries and most frequent indications for LS CS were nonprogress of labor (8/35), breech presentation (8/35) and fetal distress (6/35). 10 (7.4%) babies were born preterm. 23 (17%) babies were born low birth weight. 37 (27.4%) neonates were symptomatic and required neonatal admission. Respiratory distress was the most frequent neonatal problem (29; 21.5%), followed by neonatal sepsis (18; 13.3%) and perinatal asphyxia (9; 6.7%). There were 3 (2.2%) still birth and 2 (1.5%) early neonatal deaths. Conclusion: Adolescent pregnancy was common and associated with increased early neonatal problems.